Mediação como instrumento de desjudicialização das questões familiares: constitucionalização do Direito de Família - Guerra, Nara Rúbia Silva Vasconcelos (2013)
The Liberal Constitutionalism emerged from the late eighteenth century, a period of major revolutions (French and American), fruit of the struggle for libertarian rights. Although the time of the first written constitutions, these were linked to mere political letters, did not provide for fundamental human rights, as it is, so only on the state organization, structure of powers, division of powers of the state and some relations between state and individuals. There was a clear division between the civil codes and constitutions, those governing private relations and acted as barriers to non-state intervention. After the Second World War, the constitutions are no longer Letters political order to establish how the human person, in order to enshrine the fundamental rights, the primacy of constitutional principles and take their normative function against ordinary legislator. Constitutional evolution gave the name of contemporary constitutionalism, based on repersonalization or despatrimonialização of Private Law, ceasing the separation of legislative civil codes and constitutions, in favor of the protection of fundamental rights of the human person. And this tendency to the Brazilian Federal Constitution of 1988 brought higher ground the dignity of the human person, the epicenter axiological legal to govern private relations, including family law. The constitutionalization of family law motivates the adoption of desjudicialização family issues, so as to respect the direio intimacy, privacy, private autonomy and access to justice. Conflictual family relationships require special treatment, given the diversity and dynamism of their new compositions. The break in the family relationship is guided in varied feelings among its members in order to hinder an end harmonic. Thus, the judiciary, through performances impositive, not to honor the power of decision of the parties, as also on the structural problems faced to operate on these cases, the environment is not the most appropriate to offer answers to the end of family quarrels. Situation that causes future demands on the dissatisfaction of the parties with the result. Before the development of the Family Law comes the need to adopt legal institutions, which monitor the socio-cultural, and that promote an effective assistance to people involved in this kind of conflict. In obedience to the private autonomy, before manifestations of volunteers involved in family mediation, among autocompositivos instruments of conflict resolution, is indicated as the most shaped the treatment of family quarrels. Remaining, then the state a minimal intervention to prevent excessive intrusion into private life and personal privacy